Russian editions of the XIX century in the University Library collection in Warsaw - Z. .. Ol’Chak (Библиосфера, 2016)
The article first represents results of the quantitative analysis of the Russian XIX century editions stored in the collection of the University Library in Warsaw. The research objective is to check the view, settled in bibliology, regarding it as the owner of one of the largest collections of the Russian books and magazines outside Russia. Calculations were carried out with the library card catalogs - the Chief alphabetical one and the Catalog of periodicals.